Analisis Pelaksanaan Program Stabilisasi Bayi Asfiksia Oleh Bidan di Puskesmas Kota Parepare - Harima M; Martha Irene Kartasurya; Siti Fatimah (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Infant mortalities in Parepare City in South Sulawesi in 2014 were mostly caused by asphyxia (31%). The places of these mortalities with asphyxia occurred among infants aged less than or equal to 48 hours after birth were at health centres (46%) and at referral units (54%). This problem was due to unoptimal stabilisation program for asphyxia babies. The aim of this study was to analyse the implementation of the stabilisation program of asphyxia babies by midwives at health centres in Parepare City. This was a qualitative study. Main informants consisted of implementer midwives at health centres who had followed training of asphyxia management (10 persons). Informants for triangulation purpose consisted of coordinator midwives, heads of health centres, head of maternal and child health sections at Parepare City Health Office (CHO), and asphyxia babies’ families. Three health centres with the highest asphyxia baby mortality rate in Parepare City were selected. Data were collected by conducting indepth interview and analysed using a method of content analysis. The results of this research showed that the stabilisation program of asphyxia baby by midwives had not implemented two of six components namely components of blood sugar stabilisation and laboratory analysis. These condictions were due to communication aspects like lack of clarity and lack of information consistency about the program. Meanwhile, viewed from the aspect of disposition/attitude, there were lack of midwives’ commitments in implementing the program, lack of trained health officers, no specific budget, lack of facilities, and no mechanism of reporting and Standard Operating Procedure (SOP) for implementing the program. Parepare CHO needs to provide training for implementer midwives about stabilisation of asphyxia baby, to increase socialisation of the program to implementer midwives, and to arrange SOP and a report form.